Narratives of the Russian-Ukrainian conflict in the Italian press and social media - Gozzo, Simona; Fragapane, Stefania (Frontiers in Sociology, 2025)
This contribution, focused on narratives of the Russian-Ukrainian conflict, was carried out on an annual basis of articles published in two of the main Italian newspapers (in the online version), and of comments extracted from Twitter/X. The work looks at communication structure, language and content, and at possible points of contact between the two sources, as different forms of communication: one unidirectional and institutional, the other potentially bidirectional and choral. To understand the representations of the war in the press, we chose to focus on news headlines, due to their ability to capture attention through their language, which is generally direct and clear, and capable of summarising the content of the article. The selection of Twitter to reconstruct users’ opinions is due, instead, to the specific role played by this platform in capturing opinions and attitudes with respect to the news disseminated by the selected newspapers. Useful information is extracted, with particular attention to the contents (it is thus preferred to reduce the number of comments by avoiding sentiment analysis in favour of a more controlled automatic content analysis procedure). The results show greater heterogeneity of sources and thematization on Twitter/X.